Biotechnology and the Green Future of Reproductive Health: Innovations for an Environmentally Sustainable Approach - Sarbasheva Marziyat; Khamchiev Kureysh; Isaeva Petmat (BIO Web of Conferences)
In the face of global environmental challenges and the imperative to promote sustainability, the intersection of biotechnology and reproductive health presents an opportunity for innovative solutions. This paper explores the potential of integrating biotechnological advancements into reproductive health practices to foster environmentally sustainable approaches. By examining emerging technologies such as eco-friendly fertility treatments, biodegradable contraceptives, and sustainable reproductive tissue preservation methods, this study highlights how biotechnology can contribute to reducing the environmental footprint of reproductive health interventions. Additionally, it discusses the ethical considerations, regulatory frameworks, and societal implications associated with the adoption of these technologies. Ultimately, this paper envisions a green future for reproductive health, where biotechnology plays a pivotal role in promoting both human well-being and environmental stewardship.